The non-observance of Grice’s Maxims in the creation of humour in a Chinese sitcom / Zhao Xue - Zhao, Xue (2017)
Sitcoms provide entertainment, one of which is through humour. This study focuses on how humour was created in a few episodes of a selected Chinese sitcom - Home with Kids (Season 4). Using Grice’s (1975) non-observance of Cooperative Principles – flouting, violating, infringing, opting out, and suspending as framework for analysis, the study aims to understand which type of non-observance and maxim played an important role in creating humour. Data were compiled from 96 episodes and a comparison of the non-observances was made before findings were qualitatively presented. The outcome of the study indicates that not all the maxims were observed in generating the humour effect. Among the non-observances noted, flouting and violating appear to be used most frequently, with the Maxim of Quality being cast as the most preferred manner of creating humour. The outcome of this study will benefit learners who take Mandarin as a second or third language, and help them to comprehend Chinese humour better.